The theory on the natural elements in the philosophical and theological system of the Byzantine thinker George Pachymeres - Petridou, Lydia; Terezis, Christos (De Medio Aevo, 2022)
In this paper we discuss the general question on how a Byzantine philosopher-theologian of the late Palaeologan Renaissance forms some aspects of Natural Science. Specifically, focusing on George Pachymeres’ Paraphrasis of Pseudo-Dionysius the Areopagite’s De divinis nominibus, we investigate how this philosopher builds his theory on the natural elements (earth, air, water, fire). We raise a number of questions that have to do with the way in which the elements exist, what is their relation to matter, how causality works in this case and whether priority is given to Ontology or Epistemology. From a methodological point of view, we approach the text scientifically, philosophically and theologically. The most important conclusion that we draw is that in this commentary George Pachymeres’ references on the elements can be placed into three categories (the elements 1. as the products of the divine energies; 2. as cosmological sources; 3. as allegorical names), depending on the context. Finally, we can contend that, although he does not present here a systematic theory on the elements, the Byzantine thinker, who has a thorough knowledge of both the Platonic and Aristotelian tradition, manages to conceive the concept of the “element”.